Pengaruh perbedaan mengunyah buah stroberi (Fragaria vesca L.) dan buah apel (Malus sylvestris Mill ) terhadap penurunan indeks plak pada anak-anak - Monang Panjaitan; Natasya Soraya; Fadilah Romadonna Harahap (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2019)
The accumulation of plaque on the tooth surface as an indicator of oral hygiene. Plaque control can be done mechanically or chemically. Mechanically, control of plaque by brushing and flossing, while chemical plaque control can be done by consuming fruits. Apples and strawberries are indicated to reduce the plaque index. The main objective of this study was to analyze the effect of differences in strawberry and apple chewing on a decrease in dental plaque index. This research is an intervention study with pre test and post test control group design. The research population was 130 children of the Thank Kasih Abadi Orphanage. The research sample amounted to 32 respondents who had met the inclusion criteria by dividing two groups, namely 16 respondents chewing strawberries and 16 other respondents chewing apples. The results showed that there were differences in the effect of chewing strawberries (Fragaria vesca L.) and apples (Malus sylvestris Mill) on decreasing the plaque index in children of the Thank You Eternal Orphanage (p = 0.037). The conclusion of this study is that mastication of apples proved to be more effective in lowering the plaque index than chewing strawberries.